What do Latin Americans think of the IDB? - Marina Bassi (Inter-American Development Bank, Research Department, 2007)
Using the Latinobarómetro survey, this paper examines Latin Americans' perceptions of the IDB, the World Bank and the IMF. The study analyzes how people's knowledge and evaluation of these multilateral organizations are affected by the demographic and socioeconomic characteristics of the respondents, the country where they live, the financial position of the IDB in that country, macroeconomic conditions and interviewees' political orientation and attitudes towards democracy and free markets. The results indicate both good and bad news for the IDB. Negatively, it is the least-known of the three international organizations; but positively, it is the best rated among those familiar with them. Demographic variables and socioeconomic levels are important determinants of who knows these organizations. In terms of grading, the demographic characteristics of the respondent seem to have no impact. Conversely, economic status, macroeconomic conditions (to some extent), and the political orientation of the respondent are significant determinants of people's evaluation.
Keywords: 330; Entwicklungsbank; Internationale Organisation; Öffentliche Meinung; Lateinamerika